Pasir Gunung Bromo sebagai Sumber Ide Penciptaan Busana Kasual - Ferita Dwi Evayanti; Imami Arum Tri Rahayu; Deny Arifiana (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
The creation of this project is based on the Practice-led Research approach through a practical study of casual fashion design with a focus on “Bromo’s Sand as an Idea Source for Casual Wear Creation”. This creation practice study aims to convey design ideas that can add different types of clothing than before. This creation was based on the beautiful and unique idea source of Bromo’s Sand, which is still very minimal to be used as a source of ideas in fashion making. To achieve the goal of creation, the practical method of creation is used through four stages, namely: exploration, design, realization and presentation. The results of this creation are 2 women's casual outfits and 1 men's casual outfit with manipulating fabric denim slashing attached to clothing using application techniques. The results of the creation were presented in a fashion show event in the courtyard of the Surabaya State University rectorate building with the concept of theatrical fashion show which raised one of the tourist and cultural destinations in the Tengger Tribe area, East Java.